National Defense - Mercado Jarrín, Edgardo (1981)
The aim of this paper is to analyze how Peru's Political Constitution of 1979 structures national defense. To this end, the articles of the Constitution relating to the subject will be examined in detail to extract the concepts of security and national objectives. It also examines the functions assigned to the president, the armed forces and the police. A comparative analysis is also made with the 1933 Constitution in order to highlight the differences and to emphasize the new roles assigned. Finally, it is concluded that the 1979 Constitution places greater limitations on the exercise of the functions of the armed forces, providing a clearer and more specific framework for their actions and redefining their role in national defense and security.